Uji Efek Teratogenik Infusa Daun Kopi Arabika (Coffea arabica L.) Terhadap Fetus Mencit - Afriyeni, Helmice; Yosmar, Rahmi; Rizal, Rosiana; Fikri, Zahiya Afifah (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2025)
Arabica coffee leaves (Coffea arabica L.) are a herbal medicine used to treat hypertension, diarrhea, malaria, fever, diabetic and hypercholesterolemia. However, it is feared that the use of herbal medicines will cause side effects during pregnancy, especially defects in the fetus. This concern arises due to the lack of information regarding the side effects and toxicity of herbal medicines. Therefore, it is necessary to conduct research on the teratogenic effects of Arabica coffee leaf infusion (Coffea arabica L.) on test animals. This study used varying concentrations of Arabica coffee leaf infusion of 2.5%, 5%, and 10%, which were given orally during the organogenesis period of white mice (Mus Musculus) pregnancy, days 6-15 of pregnancy. On the 18th day, a laparotomy was performed, then the fetus was observed to see whether there were skeletal and external malformations. The statistical results of one-way ANOVA show that there is an abnormality in the fetus in the form of low birth weight (LBW), and the incidence of fetal death increases with each administration of a larger concentration/1 infusion. Statistical results of two-way ANOVA showed that the concentration and length of treatment significantly influenced the mother's body weight (P<0.05), while the interaction between the two had no significant effect (P>0.05). The research results show that Arabica coffee leaf infusion has the potential to have a teratogenic effect on the fetus.